2003
DOI: 10.1002/hyp.1289
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and metal concentrations, size distributions and fluxes in major rivers of the Amazon basin

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…This relationship corresponds with the observed temperature dependence of both bacterial decomposition and Colorado River Decrease in lower section 2300Miller, 2012 photochemical oxidation (Davidson and Janssens, 2006;Porcal et al, 2015)-the two major pathways for in situ DOC loss in aquatic systems (Cole et al, 2007). The lower coefficient of correlation between DOC concentration and temperature in the UMR (4c) was probably due to additional DOC loss pathways, such as sorption onto particles (Aufdenkampe et al, 2001), DOC flocculation (Benedetti et al, 2003) and exchanges with floodplains (Tockner et al, 1999). Meanwhile, we also found that contributions from tributary dilutions on DOC decreases were all positively correlated with water discharge in both river sections (Figures 4A,B).…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 73%
“…This relationship corresponds with the observed temperature dependence of both bacterial decomposition and Colorado River Decrease in lower section 2300Miller, 2012 photochemical oxidation (Davidson and Janssens, 2006;Porcal et al, 2015)-the two major pathways for in situ DOC loss in aquatic systems (Cole et al, 2007). The lower coefficient of correlation between DOC concentration and temperature in the UMR (4c) was probably due to additional DOC loss pathways, such as sorption onto particles (Aufdenkampe et al, 2001), DOC flocculation (Benedetti et al, 2003) and exchanges with floodplains (Tockner et al, 1999). Meanwhile, we also found that contributions from tributary dilutions on DOC decreases were all positively correlated with water discharge in both river sections (Figures 4A,B).…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 73%
“…Dissolved and suspended phases were isolated immediately on board by filtration through 0Ð2 µm membrane filters using an ultra-clean procedure described elsewhere (Seyler and Elbaz-Poulichet, 1996). In addition, water samples were collected in the mixing zone at various depths (1, 6, 15, 25, 35, 45 m) and distances from the river bank ( Figure 3) and treated on board by a sequential cross-flow ultrafiltration (Eyrolle et al, 1996;Benedetti et al, 2003). For samples, 2 l of water were filtered using clean 0Ð2 µm (P 1 ) and 5 kDa (P 2 ) ultrafiltration membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Floodplains and lakes often represent areas of enhanced primary production, providing the river with fresh autochtonous OM (Junk et al, 1989;Melack and Forsberg, 2001;Benedetti et al, 2003). High levels of algal and aquatic plant production (Junk and Howard-Williams, 1984;Junk et al, 1989) can considerably enhance the overall export of DOM from a river system (Tockner et al, 1999;Hedges et al, 2000).…”
Section: Conversion Of Om To Co 2 In Inland Watersmentioning
confidence: 99%